(untitled) (Applied Biological Research, 2012)
Eupatorium cannabinum L. (Asteraceae), a common wild plant growing in high altitude areas of Asian and Europian continents, is a well known traditional medicinal plant used as a source of alternative medicine and febrifuge. Herbalists have recognize its wound healing, cathartic and diuretic properties. The herb when used either alone or in combination with other herbs is a good remedy for purifying blood. Its leaves contain a volatile oil compound which acts on kidneys, and likewise some tannin and a bitter chemical principle are present which cut short the chill of intermittent fever. The chemical constituent and pharmacological studies of the herb in rats have revealed its choleretic and hepatoprotective properties (Zdero and Bohlmann, 1986; Lexa et al., 1989). Investigations on anti